SGCMG Non-Singularity Trajectory Programming Algorithm based on Improved CVP Method - Mao, Shaojie; Wang, Hao; Jin, Zhonghe (IEEE Advanced Information Technology, Electronic and Automation Control Conference (IAEAC) (Online), 2021)
As the preferred satellite maneuver actuator, single gimbal control moment gyroscope (SGCMG) has singular problems in the process of attitude maneuver. In this paper, a new algorithm for SGCMG singularity avoidance is designed based on the control variable parameterization (CVP) algorithm. Firstly, the sensitivity equation of the system is defined- and approximated by the piecewise constant. Then, the time unit to be refined is selected according to the sensitivity of the objective function to the control parameters, and the number of time nodes meeting the accuracy requirements is obtained. This method only needs simple velocity control for frame servo system. Finally, simulation results showed that, in the process of trajectory planning, a trajectory curve with stable attitude parameters and satellite angular velocity can be planned out by setting practical constraints in engineering, considering energy resources and target accuracy comprehensively, and there will be no singularity in SGCMG.